The Effect of H2SO4 Concentration on the Yield and Purity of Zinc Sulfate in the Synthesis of Zinc Sulfate from Zinc Waste - , Sunardi; , Sumardiyono; Mahayana, Argoto; Hidayati, Nur; , Soebiyanto; Dewantara, Mahardira; Afghohani, Afif (Jurnal Serambi Engineering, 2026)
Zinc waste is a type of waste that comes from the use or production of zinc metal. Zinc waste is widely used in the production of paint, ceramics, glass, lamps, and pesticides. Zinc waste is very dangerous if not properly processed/utilized. If disposed of in large quantities into waterways, zinc waste can cause environmental pollution. Zinc waste is actually needed in water, but only in very small amounts. If the zinc content in water exceeds the specified threshold, it will be dangerous and toxic to living organisms. Excess zinc waste will damage the aquatic and soil ecosystems, which will certainly also have an impact on the health of living creatures and pose health risks to humans, such as digestive disorders and damage to certain organs. To reduce the amount of zinc waste, it is necessary to synthesize zinc waste into zinc sulfate. The purpose of this study was to determine the effect of sulfuric acid concentration on the yield and purity of zinc sulfate from zinc waste. The synthesis process includes pre-treatment, which is carried out by reducing the size of the zinc waste, then soaking the zinc waste in hydrochloric acid (HCl) to dissolve the oxide layer contained in it, cleaning the zinc surface of crusts, and separating the zinc from its mixture. Then, the synthesis process is carried out using a sulfuric acid (H2SO4) solution with varying concentrations (20%, 30%, 35%, and 45%) with heating at a temperature of 75-80° C and stirring at a speed of 300-350 rpm. Filtration is then carried out, and the filtrate obtained is heated until the solution becomes saturated, followed by a crystallization process. It is cooled to room temperature, and zinc sulfate crystals are obtained. In this study, white zinc sulfate heptahydrate (ZnSO4.7H2O) was obtained using a 45% sulfuric acid (H2SO4) solution, yielding a weight of zinc sulfate heptahydrate (ZnSO4.7H2O) of 3.1729 grams, a ZnSO4.7H2O concentration of 52.80% and the purity level of ZnSO4.7H2O was 96.28%.